The Prevalence of Some Epidemic Leishmania Spp. Isolated from Human Blood and Skin Samples - F. Hamoodi, Hadeer; B. Aldeen, Muna; M. Aliwi, Nada; H. Abdulkhaliq, Sally (Al-Nahrain Journal of Science, 2025)
Leishmaniasis ranks as the second deadliest parasitic disease globally, following malaria. Recognized by the World Health Organization as a neglected tropical disease, leishmaniasis continues to pose a major public health challenge. This study aimed to evaluate the sensitivity and specificity of the Direct Agglutination Test as a diagnostic tool for leishmaniasis. A total of 666 dried blood samples were collected between March 7 and June 21, 2024. These included606 samples from suspected visceral leishmaniasis cases, 63 from cutaneous leishmaniasis cases, 66 from healthy individuals as controls, and 63 from individuals with other medical conditions. The study focused on three main objectives: evaluating the Direct Agglutination Test using locally prepared Leishmania antigens (L. donovani, L. tropica, and L. major), identifying sandfly species, and monitoring their seasonal population densities. The Leishmania antigens were prepared using mercapto-ethanol and glutaraldehyde. The direct agglutination test demonstrated 100% sensitivity in confirmed cases of visceral leishmaniasis when using the L. donovani antigen, and 93% sensitivity in clinically suspected cases. For cutaneous leishmaniasis, the L. tropica antigen also achieved 100% sensitivity. In contrast, traditional diagnostic methods—such as smears and cultures—yielded lower positivity rates, at 60.16% and 69.46% respectively. Among the antigens tested, L. tropica showed the highest specificity at 96.19%, followed by L. donovani at 87.68%. Cross-reactivity with sera from individuals with other diseases was minimal. Visceral leishmaniasis was most prevalent among children under five years old, while cutaneous cases were more common in the 6–30 age group. Males were more frequently affected in both forms of the disease. Visceral leishmanias is cases were predominantly reported in rural areas, whereas cutaneous cases were more common in urban settings. Most cutaneous lesions (96.6%) were single and primarily located on the face and upper limbs. The direct agglutination test outperformed the indirect method in sensitivity and specificity, proving its effectiveness for diagnosing leishmaniasis.